Mechanism and Disease Association With a Ubiquitin Conjugating E2 Enzyme: UBE2L3 - Zhang, Xiaoxia; Huo, Chengdong; Liu, Yating; Su, Ruiliang; Zhao, Yang; Li, Yumin (Frontiers in Immunology, 2022)
Ubiquitin conjugating enzyme E2 is an important component of the post-translational protein ubiquitination pathway, which mediates the transfer of activated ubiquitin to substrate proteins. UBE2L3, also called UBcH7, is one of many E2 ubiquitin conjugating enzymes that participate in the ubiquitination of many substrate proteins and regulate many signaling pathways, such as the NF-κB, GSK3β/p65, and DSB repair pathways. Studies on UBE2L3 have found that it has an abnormal expression in many diseases, mainly immune diseases, tumors and Parkinson’s disease. It can also promote the occurrence and development of these diseases. Resultantly, UBE2L3 may become an important target for some diseases. Herein, we review the structure of UBE2L3, and its mechanism in diseases, as well as diseases related to UBE2L3 and discuss the related challenges.